Risk Factors of Dengue Fever: Application of PRECEDE - Kanthi Devi Ayuningtyas; Setyo Sri Rahardjo; Bhisma Murti (Masters Program in Public Health, 2019)
Background: Dengue infection is one of the main health problems in more than 100 tropical and subtropical countries. This study aims to analyze the factors that play a role in the occurrence of dengue fever cases by applying the PRECED - PROCEED model.Subjects and Method:This was an analytic observational study with a case control design. The study was conducted at 8 sub-districts in Sukoharjo, Central Java, from May to July 2018. A sample of 200 study subjects was selected for this study by fixed disease sampling, comprising 50 peoples with dengue fever and 150 peoples without dengue fever. The dependent variables were dengue fever. The independent variables were intention, attitude, education, dengue fever prevention, family income, and sanitation. The data were collected by questionnaire and analyzed by path analysis run on Stata 13.Results: The risk of dengue fever was directly reduced by good environmental sanitation (b= -1.32, 95% CI= -2.09 to -0.54, p= 0.001) and good prevention behavior (b= -2.61, 95% CI= -3.55 to -1.67, p<0.001). The risk of dengue fever was indirectly affected by intention, attitude, education, and family income.Conclusion: The risk of dengue fever is directly reduced by good environmental sanitation and good prevention behavior. The risk of dengue fever is indirectly affected by intention, attitude, education, and family income.Keywords: dengue fever, preventive behavior, environmental sanitation, PRECEDE-PROCEED modelCorrespondence: